Role of Ultrasonography in Predicting Gastro-oesophageal Varices in Patients with Liver Cirrhosis - Gyawali, Merina; Acharya, Ramesh Raj (Journal of College of Medical Sciences-Nepal, 2021)
IntroductionUpper Gastrointestinal endoscopy is considered the best screening tool in detecting gastroesophagealvarices in patients with cirrhosis. Ultrasonography of the abdomen can be used forassessment of liver and portal system. This research was undertaken to demonstrate that theportal vein diameter and splenic size by ultrasonography can be used as a non-invasive predictorof gastro-esophageal varices.MethodsA cross-sectional hospital based study comprising of 290 consecutive patients with liver cirrhosiswere enrolled between November 2019 to November 2020. Clinical profile at admission andsonological splenic size and portal vein diameter were studied in all cirrhotic patients. Patientswere classified into 2 groups: one with presence of varices and second without varices. Data entrywas done in Statistical Packages for the Social Sciences version 20.ResultsThe mean age of subjects was 52±13.26 years with a range of 27 – 82 years of age (M:F=2:1). Thecommonest etiology of cirrhosis was chronic alcohol consumption. The prevalence of varices incirrhotics was 42.8%. Average portal vein diameter of patients without gastro-esophageal variceswas 11.12 ± 1.36 mm, while it was 12.81 ± 1.62 mm in patients with varices (p < 0.001). Averagespleen size in cirrhotics without varices was 12.44 ± 1.32 cm and with varices was 14.32 ± 2.42 cm.This difference was also statistically significant (p < 0.001).ConclusionsMeasurement of portal vein diameter and spleen size by ultrasonography can be recommendedas a non invasive predictor for gastro-oesophageal varices in patients with liver cirrhosis .Keywords: cirrhosis; portal vein diameter; spleen size; ultrasonography; gastro-oesophageal varices